Telmatobius rubigo occurrence points - Akmentins, Mauricio Sebastián (2023)
Datos de ocurrencia de Telmatobius rubigo, registrados en sucesivas campañas de campo realizadas en la Puna de Jujuy, Argentina. Occurrence points of the threatened rusted frog T. rubigo were compiled and curated from field observations through an active search by visual encounter carried out from 2016 to 2023.